Shaking table investigation of inelastic deformation demand for a structure isolated using friction-pendulum sliding bearings. (June 2021) - Tsiavos, Anastasios; Markic, Tomislav; Schlatter, David; Stojadinovic, Bozidar
Abstract: This study aims at investigating experimentally if seismically isolated structures can manifest inelastic behavior when they are subjected to strong earthquake ground motion excitation. A steel structure is seismically isolated with four friction pendulum bearings and subjected to an ensemble of recorded earthquake ground motion excitations using the shaking table of ETH Zurich Laboratory. The structure is designed to concentrate its inelastic behavior on a mechanical clevis connection comprising two hinges and a pair of replaceable steel coupons. The use of this configuration enables the adjustment of the strength of the structure and thus the parametric investigation of its displacement ductility demand µ for a wide range of earthquake ground motion excitations. The experimentally derived values of the ductility demand µ for the seismically isolated structure are compared with the analytically determined values obtained through the use of Ry - μ-Tn relations for fixed-based structures and the corresponding relations developed for seismically isolated structures.